PELATIHAN FISIK SEIMBANG MENINGKATKAN AKTIVITAS STEM CELL ENDOGEN UNTUK ANTI PENUAAN - Milas Siswanto, Ferbian; Pangkahila, Alex (Sport and Fitness Journal, 2014)
Human life expectancy increasing progressively declines with technological developments and poor lifestyle. The cause of death due to an unhealthy lifestyle among other physical activity that is not in accordance with scientific principles accelerates the aging process. The development of the science of Anti - Aging Medicine is expected to improve human welfare through increased life expectancy. Several attempts have been made, both in research and clinical reports, to find the factors of aging that can do prevention and control. These efforts are expected to be a reference to slow down the aging process and preventing the aging occur. One of the efforts that have been made in various countries is the use of stem cells. The utilization of stem cells is a breakthrough in the field of medicine to address degenerative diseases and slow down the aging process. The ability of proliferation, differentiation and self- renewal of stem cells can be used to replace the cells, tissues, and organs damaged by the aging process. The characters and the unique benefits of this increase the number of stem cell field research. One area of ??research that is related to the formation of the stem cell is physical exercise factor. The benefits of physical training on endogenous stem cells give new hope in the field of anti - aging medicine. Regular physical training in accordance with scientific principles (exercise physiology), is expected to prevent anti-aging through activation of endogenous stem cells in the body naturally.
Keywords: Anti-aging, endogenous stem cell, and physical exercise.